PENGEMBANGAN COMIC DIGITAL BERBASIS LINGKUNGAN SEKITAR DALAM PEMBELAJARAN IPA TERPADU - Mochammad Iqbal; Pramudya Dwi Aristya Putra (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
The purpose of this study is to develop environment based digital comic as learning media in integrated science lesson. In this study, there are four development steps; surveys and needs analysis, product development, expert validation and a limited field test. Surveys conducted by taking questionnaire to 25 students who have attended in integrated science course. Based on the surveys result, we develop learning media in two stages: developing comic design then uploading into e-learning program. Field test subject is Physics education study program, that attended in  integrated science course. The result of this study shows that environment based digital comic can be used in the process of learning both in the classroom or self-study, with good scores both in expert validation and limited field test. This media can be applied in online learning process. Keywords: digital comic, environtment, integrated science